Synthesis and evaluation of novel 1,3,4-thiadiazole-fluoroquinolone hybrids as antibacterial, antituberculosis, and anticancer agents - TÜRE, ASLI; TATAR, ESRA; KÜÇÜKGÜZEL, İLKAY (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY-TUBITAK, 2018)
A series of 5-substituted-1,3,4-thiadiazole-based fluoroquinolone derivatives were designed as potential antibacterial and anticancer agents using a molecular hybridization approach. The target compounds 16-25 were synthesized by reacting the corresponding N-(5-substituted-1,3,4-thiadiazol-2-yl)-2-chloroacetamides with ciprofloxacin or norfloxacin. The purity and identity of the synthesized compounds were determined by the use of chromatographic and spectral techniques (NMR, IR, MS, etc.) besides elemental analysis. Antibacterial, antituberculosis, and anticancer activity of the target compounds were evaluated against selected strains and cancer cell lines. Compound 20 was appreciated as the most active agent representing antibacterial activity against Escherichia coli and Staphylococcus aureus with MIC values of 4 mu g/mL and 2 mu g/mL, respectively. Amongst the synthesized fluoroquinolone derivatives, compounds 19 and 20 were found to have modest antitubercular activity with 8 mu g/mL MIC values for each. Most potent derivative, compound 20 was docked against Staphylococcus aureus and Mycobacterium tuberculosis DNA gyrase enzymes to visualize the possible conformation of the compound. Additionally, anticancer activities of target compounds were evaluated on seven different cancer cell lines.
Keywords: Fluoroquinolones; 1,3,4-thiadiazoles; antibacterials; tuberculosis; DNA gyrase; molecular modeling; cytotoxicity; BIOLOGICAL EVALUATION; POTENTIAL ANTITUMOR; ANTIMYCOBACTERIAL ACTIVITIES; NONNUCLEOSIDE INHIBITORS; TOPOISOMERASE-I; DRUG DISCOVERY; CIPROFLOXACIN; FLUOROQUINOLONES; DERIVATIVES; QUINOLONE